2012
DOI: 10.4102/sajems.v15i4.251
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the venture creation phases in terms of entrepreneurial self-efficacy: links to competitiveness of South African ventures

Abstract: Examining entrepreneurial self-efficacy across venture creation phases is important as research indicates that behaviours to which self-efficacy corresponds are largely concerned with new-venture formation processes and as such are required of entrepreneurs well beyond the point of founding. Hypotheses are formulated, which take into account the sequential nature of entrepreneurial tasks in the venture process. A multidimensional instrument is used to collect data from medium businesses (n = 199). Correlationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
1
11
0
1
Order By: Relevance
“…For example, the results of McGee et al's (2009) study suggest that nascent entrepreneurs' confidence in performing "searching" tasks develops before gaining confidence in tasks that come later in the new venture creation process such as planning, marshaling of resources, and implementing (McGee et al 2009). Urban (2012) reported similar findings in his study of South African entrepreneurs. New ventures lead by entrepreneurs who were confident in their searching and planning abilities enjoyed higher competitiveness than their counterparts lead by less confident entrepreneurs.…”
Section: Theoretical Backgroundsupporting
confidence: 77%
See 1 more Smart Citation
“…For example, the results of McGee et al's (2009) study suggest that nascent entrepreneurs' confidence in performing "searching" tasks develops before gaining confidence in tasks that come later in the new venture creation process such as planning, marshaling of resources, and implementing (McGee et al 2009). Urban (2012) reported similar findings in his study of South African entrepreneurs. New ventures lead by entrepreneurs who were confident in their searching and planning abilities enjoyed higher competitiveness than their counterparts lead by less confident entrepreneurs.…”
Section: Theoretical Backgroundsupporting
confidence: 77%
“…Another salient stream of research relies on a four‐phase, sequential new venture creation framework to demonstrate that ESE is a multi‐dimensional construct that influences both successful venture creation and subsequent venture performance (McGee et al ; Mueller and Goic ; Urban ). The framework's phases include: (1) searching; (2) planning, (3) marshaling; and (4) implementing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…personnel and human resources aspects of implementation, and, (5) implementing-finance i.e. financial aspects of implementation (Urban, 2012). The dimensions were empirically tested using a sample of adults in the USA and found that each of the dimensions of ESE was positively related to attitude to entrepreneurship and nascent behaviour.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Thirdly, the paper explores EI of final year students in Zambia and therefore represents a valuable contribution to African entrepreneurship research. Besides a few studies on Africa such as in South Africa (Malebana and Swanepoel, 2014;Urban, 2006Urban, , 2012) and in Ethiopia (Gerba, 2012), extant literature reveals that research on EI, nascent behaviour and self-efficacy is mainly conducted in developed countries; developing countries, especially Africa, and that includes Zambia, are under-researched (Fayolle and Liñán, 2014;Hoskisson et al, 2011;Liñán and Fayolle, 2015;Mwiya et al, 2017). This constrains generalisability of the prior research conclusions.…”
Section: Contributions and Practical Implicationsmentioning
confidence: 99%
“…For instance, entrepreneurial self-efficacy is an important motivational construct that influences individual choice, goals, and emotional reactions, as well as the persistence of rural entrepreneurs in Africa (Urban, 2012). Other studies emphasize social structure and the importance of social capital, family ties, and communal orientation as a driving force for entrepreneurship (George, Kotha, et al, 2015;Khayesi et al, 2014).…”
Section: Entrepreneurship In the Informal Economymentioning
confidence: 99%